Implementasi Royalti Terhadap Pencipta Lagu Berdasarkan Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta - Daffa Okta Permana; Esther Masri; Clara Ignatia Tobing (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2021)
Indonesia is a country that has a thousand islands that have a wide diversity of arts and culture and are rich in ethnic, ethnic, national and religious diversity. The wealth of art and culture is a national potential that must be protected. Intellectual works of artistic and cultural property that can and need to be protected by law. Because this protected artistic and cultural wealth can increase the welfare not only for its creators but also for the nation and state. This study aims to see how the implementation of Law No. 28 of 2014 on Copyright and what legal remedies are if the songwriter does not get his economic rights. This research uses juridical-normative research which is carried out by tracing or analyzing and analyzing theoretical matters concerning principles, conceptions, legal doctrines and norms, library materials or document materials. The results of this study indicate that the implementation of Law Number 28 of 2014 concerning Copyright is still far from good, because there are still many songwriters who do not get royalties from the songs they create, so many songwriters take legal efforts to get royalties from songs. which he created. There is also a need for socialization to songwriters and owners of entertainment venues in order to make it easier to implement this regulation so that it can provide justice for songwriters.